Insecticide susceptibility of the dengue vector, aedes aegypti (L.) in metropolitan Bangkok - Narumon Komalamisra (2018)
Mosquito larvae were collected from the houses of dengue infected patients in Bangkok, Thailand from 55 sites (36 out of the 50 districts of Metropolitan Bangkok). Aedes aegypti larvae were tested against temephos using WHO bioassay techniques. Adult mosquitoes were tested for susceptibility to permethrin, deltamethrin, cyfluthrin, malathion and DDT using WHO diagnostic doses. Most of the larvae tested were susceptible to temephos. Only few specimens were resistant to temephos. Most adult mosquitoes were highly susceptible to malathion. Deltamethrin resistance was seen in 6 districts of Bangkok. Variable levels of susceptibility were seen with cyfluthrin. Most of the specimens showed resistance to permethrin and all specimens were resistant to DDT.